Peringkat Destinasi Dan Strategi Pengembangan Daya Tarik Wisata Pantai Di Kabupaten Bantul Yogyakarta - Atun YUlianto (Media Wisata, 2018)
The rapid development of tourism in Daerah Istimewa Yogyakarta becomes a trigger for Indonesian people to choose Yogyakarta as a destination worth visiting with a variety of potential tourism.Bantul Regency is one of the areas in the Special Region of Yogyakarta which borders directly with the Indian Ocean so that many have coastal tourist-oriented tourist destinations. Of the many beaches in the district of Bantul, each has its own beauty and characteristic respectively. Potential Attractiveness Coastal tourism in the district of Bantul in the book Tourism Statistics DIY 2016 include Parangtritis Beach, Samas Beach, Pandansimo Beach, Cave Beach Cave and Kuwaru Beach. The approach developed by the government through the Ministry of Tourism to improve the competitiveness of coastal tourism (marine) is to integrate the first dimension of infrastructure, accessibility, connectivity, activity, facilities, hospitality and market preferences. And the second is to increase synergy between local governments, business actors, and local communities (DITJEN Kerjasama ASEAN, 2015:19). However, not all the development of tourist areas can be applied in the coastal areas of Bantul regency that has a high sea wave and the proximity of the sea trough with coastal areas so it is very risky to the safety of tourists. Various complaints submitted by visitors, among others; there are still services that are not standard (expensive), there is a slum beach section, sometimes neglected discipline, clutter of land governance, multiple levies, and beach raids by various business activities make the potential of visits to coastal tourism in Yogyakarta reduced (Prasetya et al , 2015: 135). The purpose of this research is to know the most visited tourism potential and alternative tourism development strategy based on SWOT analysis. The research method used is descriptive qualitative approach. The results showed that Parangtritis Beach became the most favorite beach with the number of visitors which increased from year to year. One of the SWOT analysis of tourism development strategy in Bantul regency tourism object is by creating a special place, which is built in such a way with the background of natural panorama of the beach, to exploit the passion of swafoto visitors (selfie) as part of modern marketing through social media tourists